2012
DOI: 10.2147/dmso.s28340
|View full text |Cite
|
Sign up to set email alerts
|

Critical evaluation of the role of acarbose in the treatment of diabetes: patient considerations

Abstract: The alpha-glucosidase inhibitor acarbose has been used for more than 20 years in the management of hyperglycemia. Owing to its unique mode of action in the gastrointestinal tract, its properties are very different from other antidiabetic medications. Patients on long-term treatment to control a chronic disease are not only interested in good treatment efficacy, but are also even more interested in the safety and side effects of their medications. Significant aspects of acarbose predominantly regarding safety a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
130
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(135 citation statements)
references
References 88 publications
3
130
1
1
Order By: Relevance
“…The main reason for this is that fermentation of undigested carbohydrates by bacteria produced gas in the colon. 3) Acarbose and voglibose treatment delayed starch digestion in the small intestine but there was compensatory salvage through bacterial fermentation in the large intestine. 4) When carbohydrates (starch, dietary fiber) enter the large intestine, they are degraded by the fermentation of anaerobic flora.…”
mentioning
confidence: 98%
“…The main reason for this is that fermentation of undigested carbohydrates by bacteria produced gas in the colon. 3) Acarbose and voglibose treatment delayed starch digestion in the small intestine but there was compensatory salvage through bacterial fermentation in the large intestine. 4) When carbohydrates (starch, dietary fiber) enter the large intestine, they are degraded by the fermentation of anaerobic flora.…”
mentioning
confidence: 98%
“…The risk of hypoglycemia with DPP-4 inhibitors is low (2628). Most of the DPP-4 inhibitors are excreted by the kidneys except for linagliptin; therefore, dose restrictions may be advisable for some patients.AGIs have modest AlC-lowering effects and low risk for hypoglycemia (29). Clinical trials have shown CVD benefit in patients with impaired glucose tolerance and diabetes (14,30).…”
Section: Executive Summarymentioning
confidence: 99%
“…AGIs have modest AlC-lowering effects and low risk for hypoglycemia (29). Clinical trials have shown CVD benefit in patients with impaired glucose tolerance and diabetes (14,30).…”
Section: Executive Summarymentioning
confidence: 99%
“…This drug inhibits the upper gastrointestinal glucosidases enzymes that convert complex polysaccharide carbohydrates into monosaccharides in a dose-dependent fashion, resulting in a delayed glucose absorption and a lowering of postprandial hyperglycemia. However, gastrointestinal side effects, including mainly flatulence and sometimes soft stools or abdominal discomfort, have been reported as a limiting factor for patients treatment [41,42].…”
Section: α-Glucosidase Inhibitionmentioning
confidence: 99%